(untitled) (Journal of Shaheed Suhrawardy Medical College, 2026)
There is rising public concern of overweight as obesity has become a global pandemic. Popularity of keto diet is also rising for weight reduction . A lot of keto proponent groups, for their own commercial purpose, are attracting public attention and already made a craze about keto diet. social media is also overloaded with adds of keto products. For revealed temporary benefits, general people and even medical professionals are confused about the true consequences of it. RCTs and meta-analyses of RCTs and even umbrella review of meta-analyses reveal that the weight loss of keto diet is temporary. some metabolic and biochemical benefits are also disputed by raised LDL-C and other factors that can cause adverse cardiovascular out come.Therefore keto diet cannot be a public measure and it must be individualized and supervised by medical experts. J Shaheed Suhrawardy Med Coll 2024; 16(2): 103-106